Emulsified asphalt cold recycling functional aggregate, and preparation method and application thereof
Patent Information
- Application Number
- CN202611048141.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-15
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]针对现有乳化沥青冷再生混合料早期强度形成慢、残留水分不利于破乳与界面黏结,以及负载型增强材料在冷再生水环境中释放效率低、反应性负载物与碱性钢渣载体在存储阶段难以稳定共存等技术问题,本发明提供了一种乳化沥青冷再生功能集料的制备方法、由该方法制备得到的功能集料及包含该功能集料的乳化沥青冷再生混合料,所制备的功能集料用于乳化沥青冷再生混合料的拌和,遇水时功能集料中碱性多孔载体碱性组分催化异氰酸酯与水反应原位生成气体,气体在碱性多孔载体预留气室内膨胀将反应性负载物喷射释放,并经碱性多孔载体碱性组分催化生成聚脲,同时化学消耗体系水分,用于提高反应性负载物释放率与乳化沥青冷再生混合料早期强度、降低混合料含水率并促进破乳
[0026](1)以分步预钝化实现高活性负载物与碱性多孔载体的存储稳定共存。本发明不将多亚甲基多苯基多异氰酸酯类反应性负载物直接浸入未处理的钢渣孔隙,而是先以苯甲酰氯对碱性多孔载体孔壁进行预钝化。由于苯甲酰氯对碱性多孔载体碱性位点(游离氧化钙、氢氧化钙、硅酸钙类位点及表面羟基)的反应活性高于异氰酸酯,其在浸渍负载物之前即优先与碱性多孔载体孔壁碱性位点反应或吸附,原位生成由苯甲酸钙及残留酸组成的酸性钝化膜,在碱性多孔载体孔隙内表面构成碱性孔壁-酸性钝化膜-反应性负载物的界面层级结构。该酸性钝化膜将异氰酸酯与碱性多孔载体强碱孔壁本体隔离,使局部微环境维持酸性,从而抑制异氰酸酯在存储阶段被碱催化自聚。由此,本发明将钢渣载体碱性孔壁有利于使用阶段催化、却不利于存储阶段共存的矛盾,转化为可在时序上分离处理的可控过程。
Abstract
Description
Technical Field
[0001] This invention belongs to the field of road engineering materials technology, specifically relating to an emulsified asphalt cold recycling functional aggregate, its preparation method, and its application. Background Technology
[0002] Emulsified asphalt cold recycling technology is widely used in road maintenance and recycling due to its ability to be applied at room temperature, low energy consumption, and high utilization rate of old pavement materials. With the increasing demands for rapid traffic opening and low-carbon road construction, the requirements for the early strength and water stability of emulsified asphalt cold recycled mixtures are also becoming more stringent.
[0003] Emulsified asphalt cold recycled mixtures belong to the water-based molding system. During the construction stage, water needs to be added to ensure that the recycled asphalt pavement material and emulsified asphalt are mixed evenly. The formation of strength depends on the demulsification of emulsified asphalt and the migration and evaporation of water in the system. Under conventional maintenance conditions, this process usually takes a long time, which makes the mixture prone to problems such as low early strength, slow opening to traffic, and early susceptibility to water damage.
[0004] To accelerate early strength formation in cold recycled emulsified asphalt mixtures within a short post-mixing window, one approach is to introduce a reactive loading agent into the system that reacts with water and consumes the system's moisture. This agent is pre-loaded using porous aggregates and released after being triggered by mixing water. However, when using porous aggregates to load such reactive components, under the high moisture content and short-term high shear conditions of mixing, the mixing water easily seals the pore openings of the aggregate's micron-sized pores, hindering the release of air and the loading agent. Simultaneously, the highly reactive loading agent is prone to premature reaction, thickening, or inactivation during storage due to contact with the pore walls of porous aggregates (especially steel slag with a surface rich in alkaline components such as free calcium oxide). How to ensure the reactive loading agent remains stable during storage while being rapidly triggered and effectively released overcoming pore blockage during water-rich mixing has become a key issue restricting the application of this type of functional aggregate.
[0005] Therefore, there is an urgent need for a cold-recycled emulsified asphalt functional aggregate that can balance the long-term stable storage of highly reactive loading materials with the rapid and effective release during the mixing stage, so as to effectively solve the above-mentioned technical problems. Summary of the Invention
[0006] To address the technical problems of slow early strength formation in existing emulsified asphalt cold recycled mixtures, the unfavorable effect of residual moisture on demulsification and interfacial bonding, the low release efficiency of loaded reinforcing materials in cold recycled water environments, and the difficulty in stable coexistence of reactive loads and alkaline steel slag carriers during storage, this invention provides a method for preparing functional aggregates for emulsified asphalt cold recycled mixtures, the functional aggregates prepared by this method, and emulsified asphalt cold recycled mixtures containing the functional aggregates. The prepared functional aggregates are used for mixing emulsified asphalt cold recycled mixtures. When exposed to water, the alkaline component of the alkaline porous carrier in the functional aggregates catalyzes the reaction of isocyanate with water to generate gas in situ. The gas expands in the pre-reserved gas chamber of the alkaline porous carrier, releasing the reactive loads, which are then catalyzed by the alkaline component of the alkaline porous carrier to generate polyurea. Simultaneously, the system's moisture is chemically consumed, thereby improving the release rate of reactive loads and the early strength of the emulsified asphalt cold recycled mixture, reducing the moisture content of the mixture, and promoting demulsification.
[0007] The core technical problem to be solved by this invention is: how to make the highly active reactive loading material remain stable during the storage stage in a porous carrier containing alkaline components, and how to overcome the air lock at the pore opening of the porous carrier during the water-rich mixing stage, be rapidly triggered and effectively released, and make its release and curing process match the demulsification, dehydration and early strength formation of the emulsified asphalt cold recycled mixture.
[0008] The core technical concept of this invention is: This invention uses the alkaline component of the pore wall of the same alkaline porous carrier as the unified control core, so that it exhibits a temporal shift from acidic when stored to alkaline when used. In the functional aggregate storage stage, the alkaline components of the pore walls of the alkaline porous carrier are first pre-passivated with an acyl halide compound (benzoyl chloride). An acidic passivation film is formed in situ on the inner surface of the open pores of the alkaline porous carrier, shielding the strong alkalinity of the alkaline porous carrier body into an acidic metastable state. This allows the subsequently filled highly reactive loading material (polymethylene polyphenyl polyisocyanate) to contact the acidic passivation film rather than the strong alkaline components of the pore walls, thus achieving stable storage of the functional aggregate. In the functional aggregate usage stage, the acidic passivation film is dissolved and broken by the addition of water through mixing, causing the alkaline components of the pore walls of the alkaline porous carrier to be released back into a strongly alkaline active state. On the one hand, this catalyzes the reaction of the reactive loading material with water to generate gas in situ. The gas expands in the gas expansion chamber reserved at the pore opening of the alkaline porous carrier, changing the reactive loading material from passive displacement to active injection. On the other hand, it catalyzes the solidification of the injected reactive loading material to generate polyurea, chemically consuming the water in the system, and simultaneously consuming the free alkaline groups on the alkaline porous carrier in situ. Therefore, this invention achieves the synergistic effect of high release of reactive loads, early strength of mixtures, chemical dehydration, and anti-expansion of steel slag by using the concept of alkaline timing switch of alkaline components in the pore walls of a single alkaline porous carrier. This makes the release and solidification process of reactive loads match the demulsification, dehydration, and early strength formation of emulsified asphalt cold recycled mixtures.
[0009] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0010] A method for preparing emulsified asphalt cold recycled functional aggregate, the specific preparation steps of which are as follows:
[0011] Step S1, Loading liquid preparation: By weight, 100 parts of polymethylene polyphenyl polyisocyanate are mixed with 10-20 parts of dehydrated matrix asphalt and heated to 55-65°C, and stirred for 25-40 minutes to obtain an anhydrous loading liquid; wherein polymethylene polyphenyl polyisocyanate is a reactive component that generates gas upon contact with water and solidifies, and dehydrated matrix asphalt is used to improve the compatibility of the loading liquid with asphalt materials, adjust the viscosity of the loading liquid, and reduce premature reactions caused by free water; the anhydrous loading liquid means that the loading liquid does not contain enough free water to cause a significant premature reaction of polymethylene polyphenyl polyisocyanate;
[0012] Step S2, support pre-passivation: Based on 100 parts by weight of polymethylene polyphenyl polyisocyanate, 0.6~1.0 parts of benzoyl chloride are diluted with an inert solvent and then impregnated into a dried alkaline porous support under normal or reduced pressure, allowing it to penetrate into the open pores of the alkaline porous support. This allows the benzoyl chloride to react or adsorb with the alkaline components on the pore walls of the alkaline porous support, forming an acidic passivation film in situ on the inner surface of the open pores. Subsequently, the inert solvent and the volatile byproducts generated in the reaction are removed to obtain a support with passivated pore walls and no free acyl halide residue on the surface. The acidic passivation membrane temporarily shields the strongly alkaline sites of the alkaline components on the pore walls of the alkaline porous carrier, which is used to inhibit the direct contact between the subsequently filled reactive loading material and the alkaline components on the pore walls during the storage stage, reducing the risk of premature gelation or failure. Since this step is completed independently and removes volatile components before impregnation with polymethylene polyphenyl polyisocyanate, benzoyl chloride and polymethylene polyphenyl polyisocyanate do not coexist in the same liquid phase, thus differentiating it from the method of directly mixing benzoyl chloride into the polymethylene polyphenyl polyisocyanate loading solution and avoiding possible side reactions between the two.
[0013] Step S3, Vacuum Impregnation: The carrier with passivated pore walls and no free acyl halide residue on the surface obtained in Step S2 is placed in the loading liquid obtained in Step S1. Vacuum is drawn to a vacuum degree of -0.09~-0.098MPa and held for 10~20min. Then, the pressure is restored to normal, so that the loading liquid fills the open pores of the alkaline porous carrier and the acid passivation film is located between the inner surface of the open pores and the filled reactive loading material. An interface hierarchical structure of alkaline pore wall-acid passivation film-reactive loading material is formed in the open pores of the alkaline porous carrier. During the storage stage, the alkaline pore walls in the open pores of the alkaline porous carrier are isolated. However, after the mixing water enters the open pores of the alkaline porous carrier, the acid passivation film is diluted, dissolved and / or destabilized, so that the alkaline sites of the alkaline pore walls of the alkaline porous carrier are re-exposed, thereby triggering and promoting the reaction between the reactive loading material and water during the use stage.
[0014] Step S4, Centrifugal cavity creation: The alkaline porous carrier impregnated in step S3 is centrifuged to remove the surface liquid and part of the loading liquid at the opening of the pores, so that the filling degree of the reactive loading material retained in the opening pores of the alkaline porous carrier is less than 100%, and a reserved gas expansion cavity is formed at the opening of the alkaline porous carrier pores; thus, the opening pores of the alkaline porous carrier are not completely filled. When the mixing water enters the opening pores of the alkaline porous carrier and triggers gas generation, the gas expansion cavity provides an expansion path for the gas, forming a pressure drive from the inside to the outside in the opening pores of the alkaline porous carrier, promoting the active release of the reactive loading material to the outside;
[0015] Step S5, Encapsulation: An encapsulation layer is applied to the outer surface of the alkaline porous carrier after centrifugation in step S4 and cured to obtain emulsified asphalt cold recycling functional aggregate. The encapsulation layer reduces the entry of external moisture into the open pores of the alkaline porous carrier during storage and transportation, reducing the risk of leakage or premature reaction. During the mixing process, the encapsulation layer is locally damaged or opened under the action of collision, shearing, water wetting and compaction, allowing mixing water to enter the open pores of the alkaline porous carrier and trigger subsequent reactions.
[0016] Further preferred, in step S1, the polymethylene polyphenyl polyisocyanate is mixed with dehydrated matrix bitumen and heated to 60°C and stirred for 30 min; in step S2, the amount of the acyl halide compound is 0.8 parts, specifically one or more of benzoyl chloride, acetyl chloride, and p-nitrobenzoyl chloride; in step S3, the vacuum is drawn to a vacuum degree of -0.095 MPa and held for 15 min; in step S4, the alkaline porous carrier is centrifuged at 500~800 rpm for 30~60 s to make the filling degree of the reactive loading material in the open pores of the alkaline porous carrier 70%~85%.
[0017] Further preferably, the loading liquid in step S1 also contains one or more of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, and isocyanate prepolymer, wherein one or more of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, and isocyanate prepolymer are mixed with polymethylene polyphenyl polyisocyanate to adjust the reactivity, viscosity, and curing speed of the reactive loading material.
[0018] Further preferably, the alkaline porous carrier in step S2 is steel slag, the alkaline component of which is one or more of free calcium oxide, calcium hydroxide, and calcium silicate; the converter steel slag has a particle size of 4.75~9.5mm, an open porosity of 5%~20%, and a surface pH value ≥11; specifically, the steel slag is one or more of converter steel slag, electric furnace steel slag, treated steel slag aggregate, and calcium-containing alkaline industrial solid waste porous aggregate. The open pores of the steel slag provide storage space for reactive loading materials, and the alkaline components of the open pore walls serve as an in-situ catalytic source during the use stage.
[0019] Further preferably, in step S2, the benzoyl chloride is diluted with anhydrous toluene in an inert solvent and then impregnated with an alkaline porous support. The hydrogen chloride generated in the reaction volatilizes out or is consumed by the alkaline components of the pore wall of the alkaline porous support, and the inert solvent is removed by short-term ventilation or gentle heating. The acidic passivation membrane is composed of calcium benzoate and residual acid, which maintains the pH value of the inner surface of the open pores of the alkaline porous support at 3.0~4.0. The pH value of the inner surface of the open pores of the alkaline porous support is characterized by the pH of the extraction solution, that is, a specified mass of pre-passivated support is taken, deionized water or ethanol-water mixture is added according to a specified solid-liquid ratio, and the pH value of the supernatant is measured after extraction at room temperature for a specified time.
[0020] Further preferred, the volume of the gas expansion chamber in step S4 is 15% to 30% of the volume of the open pores; if the volume of the gas expansion chamber is too small, the gas produced by the reaction will not be able to obtain sufficient expansion stroke, and the release driving force will be insufficient; if the volume of the gas expansion chamber is too large, the load per unit mass of functional aggregate will be reduced, and the reinforcing effect may decrease; therefore, controlling the volume of the gas expansion chamber within the above-mentioned appropriate range is beneficial to balancing the load and the pneumatic release efficiency.
[0021] Further preferred, the encapsulation layer in step S5 is oxidized polyethylene wax or a mixture of oxidized polyethylene wax with one or more of polyethylene wax, paraffin wax and microcrystalline wax. The storage stability and stirring trigger sensitivity of the functional aggregate can be controlled by adjusting the composition and thickness of the encapsulation layer. The encapsulation method is spraying, rolling, dipping or hot melt coating.
[0022] This invention also provides a cold-recycled emulsified asphalt functional aggregate prepared by the above method. The functional aggregate comprises an alkaline porous carrier, an acidic passivation film located on the inner surface of the open pores of the alkaline porous carrier, a reactive loading material filling the open pores of the alkaline porous carrier, a gas expansion cavity located at the pore opening of the alkaline porous carrier, and an encapsulation layer located on the outer surface of the alkaline porous carrier. The acidic passivation film is used for interface passivation during the storage stage. During the storage stage of the functional aggregate, the alkaline components of the pore walls of the alkaline porous carrier are pre-passivated with an acyl halide compound, and an acidic passivation film is formed in situ on the inner surface of the open pores of the alkaline porous carrier. This shields the strongly alkaline nature of the alkaline porous carrier body into an acidic metastable state, allowing the subsequently filled highly reactive loading material, namely polymethylene polyphenyl polyisocyanate, to react with the acidic passivation film. The process involves contact with, rather than contact with, the strong alkaline components on the pore walls, thus achieving stable storage of functional aggregates. The reactive loading material is used for release and solidification during the usage phase. During the usage phase, the addition of water during mixing dissolves and breaks through the acidic passivation film, causing the alkaline components on the pore walls of the alkaline porous carrier to be released back into a strongly alkaline active state. This catalyzes the reaction of the reactive loading material with water to generate gas in situ. The gas expands within the gas expansion chamber reserved at the pore openings of the alkaline porous carrier, transforming the reactive loading material from passive displacement to active injection. Simultaneously, it catalyzes the solidification of the ejected reactive loading material to generate polyurea, chemically consuming the water in the system and simultaneously consuming the free alkaline groups on the alkaline porous carrier in situ. The gas expansion chamber is used for gas generation and expansion release during the usage phase. The encapsulation layer provides external protection during storage and transportation.
[0023] The present invention also provides the application of the above-mentioned emulsified asphalt cold recycling functional aggregate in the preparation of emulsified asphalt cold recycling mixtures, cold-mixed and cold-laid asphalt mixtures or cold patch materials; the functional aggregate is particularly suitable for emulsified asphalt cold recycling projects that require improved early strength, shortened time to open to traffic or improved water stability.
[0024] This invention also provides an emulsified asphalt cold recycling mixture, comprising the aforementioned emulsified asphalt cold recycling functional aggregate, recycled asphalt pavement material, emulsified asphalt, and added water. By mass percentage, the emulsified asphalt cold recycling functional aggregate comprises 20%–40%, and the recycled asphalt pavement material comprises 60%–80%; based on the total mass of the emulsified asphalt cold recycling functional aggregate and the recycled asphalt pavement material, the amount of emulsified asphalt is 3%–5%, and the amount of added water is 1%–2%; the emulsified asphalt is a cationic slow-cracking, fast-setting emulsified asphalt with a solid content ≥55%. During mixing, the added water enters the open pores of the functional aggregate alkaline porous carrier, destabilizing the acidic passivation film. The alkaline components on the pore walls of the alkaline porous carrier regain their catalytic effect, promoting the reaction of the reactive load with water. The gas generated by the reaction expands in the gas expansion chamber and pushes the reactive load out of the pores. The reactive load further reacts with water to generate a curing product containing urea groups or polyurea structures and consumes some water, thereby promoting the demulsification of emulsified asphalt and the formation of early strength.
[0025] Compared with the prior art, this invention, through the concept of alkaline sequential switching of alkaline components on the pore walls of the alkaline porous carrier, enables the alkaline pore walls, acidic passivation film, reserved gas expansion cavity, and reactive loading of the alkaline porous carrier to form a controllable synergy, which has the following advantages and beneficial effects:
[0026] (1) Achieving stable coexistence of highly active loading materials and basic porous supports through stepwise pre-passivation. This invention does not directly immerse polymethylene polyphenyl polyisocyanate reactive loading materials into the pores of untreated steel slag. Instead, it first pre-passivates the pore walls of the basic porous support with benzoyl chloride. Because benzoyl chloride has higher reactivity with the basic sites (free calcium oxide, calcium hydroxide, calcium silicate sites, and surface hydroxyl groups) of the basic porous support than isocyanate, it preferentially reacts or adsorbs with the basic sites of the pore walls of the basic porous support before impregnation of the loading material, generating an acidic passivation film in situ composed of calcium benzoate and residual acid. This forms an interfacial hierarchical structure of basic pore wall-acidic passivation film-reactive loading material on the inner surface of the pores of the basic porous support. This acidic passivation film isolates the isocyanate from the strongly basic pore walls of the basic porous support, maintaining an acidic local microenvironment, thereby inhibiting the self-polymerization of isocyanate by alkali catalysis during storage. Therefore, this invention transforms the contradiction that the alkaline pore walls of steel slag carriers are beneficial for catalysis during the use stage but not for coexistence during the storage stage into a controllable process that can be separated and processed in sequence.
[0027] (2) Stepwise feeding avoids side reactions between highly active components, unlike premixed stabilization methods. The pre-passivation of this invention is completed independently before impregnation with isocyanate, and inert solvents and volatile byproducts are removed before impregnation, ensuring that the acyl halide compound and polymethylene polyphenyl polyisocyanate do not coexist in the same liquid phase. This differs from the method of directly mixing the acyl halide compound as a stabilizer into the polymethylene polyphenyl polyisocyanate loading solution, effectively avoiding potential side reactions between the acyl halide compound and polymethylene polyphenyl polyisocyanate in the same liquid phase, and contributing to improved storage stability of the loading solution and functional aggregates.
[0028] (3) Water-induced membrane rupture forms an interface switch that is acidic during storage and alkaline during use. The acidic passivation membrane formed in this invention is not a permanent inert isolation layer, but an interface layer that can be diluted, dissolved, or / and destabilized after the addition of water during mixing. During storage, the alkalinity of the pore wall is shielded by the acidic passivation membrane and remains stable; during use, the addition of water breaks through the acidic passivation membrane, re-exposing the deep alkaline sites on the pore wall of the alkaline porous carrier. Thus, the same steel slag pore wall performs two functions at different stages: storage stability and use catalysis, achieving on-demand triggering rather than passive control dependent on external conditions.
[0029] (4) By reserving a gas chamber, passive percolation is transformed into active pneumatic injection, overcoming microscopic airlock. Traditional porous loading technology is oriented towards increasing the loading capacity and tends to fill the pores completely. In the state of full pores, the liquid is incompressible, and the gas generated when it comes into contact with water is blocked by the water film at the pore opening and cannot do work. The reactive loading material can only be passively released by diffusion and capillary percolation. This invention controls the filling degree to less than 100% by creating a cavity through centrifugation and reserving a gas expansion chamber at the pore opening. When external water is added to trigger the reaction between isocyanate and water to generate gas, the gas can expand in the gas chamber, creating pressure driving the reactive loading material in the pore from the inside out, transforming passive displacement into active injection, thereby overcoming the water film blockage at the pore opening and the airlock in the pore, and enabling the loading material to be released efficiently within the short-time stirring window of cold regeneration.
[0030] (5) In-situ alkali catalysis is used to match the curing rate with the construction window. The sprayed isocyanate is cured in the strongly alkaline environment of the re-exposed steel slag pore walls. The high concentration of hydroxide ions formed by the hydration of alkaline components in the pore walls of the alkaline porous carrier helps to reduce the activation energy of the reaction between isocyanate and water, increase the polyurea formation rate, and shorten the curing induction period, thereby facilitating the rapid establishment of structural strength within the compaction process window after mixing (approximately 10-30 minutes). This in-situ alkali catalysis changes the curing process from spontaneous and slow to relatively fast after induction, which is beneficial for matching the paving and compaction sequence of cold recycling of roads, thus facilitating the rapid opening of traffic.
[0031] (6) Chemical dehydration transforms unfavorable moisture into a reactive factor, promoting early demulsification and strength. In cold recycling systems, added water is typically a detrimental factor that delays demulsification and requires waiting for evaporation. The isocyanate of this invention reacts with water after release to generate a cured product containing urea groups or a polyurea structure. This provides gas-driven release on one hand, and chemically consumes some of the moisture in the system on the other. Thus, moisture is transformed from a passive burden waiting for evaporation into a reactive factor that triggers release and participates in strengthening, helping to reduce residual moisture content after molding and promoting demulsification of emulsified asphalt and asphalt film formation, thereby improving early strength and water stability.
[0032] (7) In-situ consumption of free calcium oxide helps to functionalize the anti-expansion properties of steel slag. The catalytic reaction in the above-mentioned use stage consumes the unstable free calcium oxide on the surface of the steel slag pore wall in situ—and free calcium oxide is one of the main causes of the volume expansion of steel slag. As a result, it helps to reduce the expansion risk of steel slag and alleviate its dependence on long-term aging treatment; steel slag is no longer just used as a general substitute aggregate, but also undertakes functions such as load, interface regulation, triggering catalysis and structural enhancement, which helps to improve the functional utilization level of solid waste.
[0033] (8) The process is continuous and the parameters are controllable, making it suitable for engineering preparation. The steps of the present invention, such as loading liquid compounding, carrier pre-passivation, vacuum impregnation, centrifugal cavity creation and packaging, can be realized by conventional stirring, vacuum impregnation, centrifugation and spraying equipment. The process is continuous and the parameters are controllable, making it suitable for large-scale preparation and road cold recycling engineering applications. Detailed Implementation
[0034] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments, but this should not be construed as limiting the invention. Unless otherwise specified, the technical means used in the following embodiments are conventional means well known to those skilled in the art, and the materials, reagents, etc. used in the following embodiments are commercially available unless otherwise specified.
[0035] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the following embodiments are only used to explain the invention and are not intended to limit the scope of protection of the invention. Without departing from the inventive concept of this invention, those skilled in the art can make conventional adjustments or equivalent substitutions to the types and proportions of raw materials, processing time, processing temperature, vacuum degree, centrifugation conditions, packaging materials, and the proportions of the mixture; all such adjustments or substitutions should fall within the scope of protection of this invention.
[0036] For ease of explanation, the functional aggregates mentioned below refer to the emulsified asphalt cold recycling functional aggregates of the present invention; the reactive loading material refers to the loading component formed by polymethylene polyphenyl polyisocyanate and dehydrated matrix asphalt, which generates gas upon contact with water and solidifies; the alkaline porous carrier is preferably steel slag.
[0037] Structure and mechanism of action of functional aggregates:
[0038] The emulsified asphalt cold recycling functional aggregate of the present invention includes an alkaline porous carrier, an acidic passivation film formed on the inner surface of the open pores of the alkaline porous carrier, a reactive loading material filled in the open pores of the alkaline porous carrier, a gas expansion cavity located at the pore opening of the alkaline porous carrier, and an encapsulation layer located on the outer surface of the alkaline porous carrier; the acidic passivation film is located between the pore wall of the alkaline porous carrier and the reactive loading material, so that an interface layer structure of alkaline pore wall-acidic passivation film-reactive loading material is formed in the open pores.
[0039] The alkaline porous carrier is specifically selected from converter steel slag, whose pore walls contain alkaline components such as free calcium oxide, calcium hydroxide, calcium silicate sites, and / or surface hydroxyl groups. These alkaline components may induce premature reaction or gelation of isocyanate-based reactive loads during storage, and can catalyze the reaction of isocyanates with water, promote gas production, solidification, and chemical dehydration during use. This invention uses an acidic passivation membrane to temporally regulate the alkalinity of the pore walls of the alkaline porous carrier, temporarily shielding it during storage and releasing it again during use by mixing with water.
[0040] During storage, the alkalinity of the pore walls of the alkaline porous carrier is shielded by an acidic passivation film. The reactive load is in contact with the acidic passivation film rather than directly with the strong alkali, thus maintaining stability. During use, external water enters the open pores, destabilizing the acidic passivation film, re-exposing the alkalinity of the pore walls, and catalyzing the reaction between the reactive load and water. The gas generated by the reaction (mainly carbon dioxide) expands in the gas expansion chamber, propelling the reactive load from inside the pores to the outside. The ejected reactive load further solidifies to form a reinforcing product containing urea groups or polyurea structures and consumes some of the water in the system, thereby promoting the demulsification and early strength formation of the emulsified asphalt. The encapsulation layer reduces the entry of external moisture into the pores during storage and transportation, and is partially damaged or opened during mixing due to collision, shearing, water wetting, and compaction.
[0041] Raw materials and testing methods:
[0042] The alkaline porous carrier uses converter steel slag coarse aggregate with a particle size of 4.75~9.5mm, an open porosity of about 10%, and a surface pH of about 12.0. It is dried to constant weight at 105℃ before use. The main reactive loading agent is polymethylene polyphenyl polyisocyanate (polymeric MDI / PAPI), which can be mixed with one or more of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, or isocyanate prepolymers. The diluent is 70# dehydrated matrix asphalt. The carrier prepassivating agent is benzoyl chloride (analytical grade), which can be applied after dilution with inert solvents such as anhydrous toluene and anhydrous n-hexane. The encapsulating material is oxidized polyethylene wax, which can be compounded with polyethylene wax, paraffin wax, and microcrystalline wax. The emulsified asphalt is cationic slow-crack fast-setting emulsified asphalt (solid content of about 60%). The recycled asphalt pavement material is milled old material.
[0043] Take 50.0g of pre-passivated converter slag with free surface reagents removed, add 200mL of deionized water at a solid-liquid ratio of 1:4 (g / mL), and extract intermittently by shaking at 23±2℃ for 30min. Take the supernatant and measure it with a calibrated pH meter. Use the pH of this extract to characterize the acidic environment of the pore walls after passivation. If necessary, ethanol-water (volume ratio 1:1) can be used as the extraction medium.
[0044] First, the volume of the open pores of the steel slag is determined by the water absorption rate method, mercury intrusion porosimetry, or microscopic image analysis. Then, the volume of the load liquid entering the pores is calculated by combining the mass difference before and after loading with the density of the load liquid. The ratio of the two is the pore filling degree. Gas expansion chamber volume percentage = 100% - pore filling degree.
[0045] Marshall specimens of emulsified asphalt cold recycled mixture were formed and tested according to the relevant test procedures: 24-hour early strength (characterized by Marshall stability), 7-day residual strength ratio after immersion in water (TSR, calculated as the ratio of stability before and after immersion in water), and residual moisture content after 24 hours of forming (drying and weighing method).
[0046] Example 1 (Best Implementation: Step-by-Step Feeding & Hole Wall Pre-passivation)
[0047] Step S1: By weight, add 100 parts of polymethylene polyphenyl polyisocyanate and 15 parts of dehydrated 70# base pitch to a reactor, heat to 60°C and stir for 30 minutes to obtain an anhydrous loading solution. Anhydrous means that the loading solution does not contain enough free water to cause a significant premature reaction of the isocyanate.
[0048] Step S2: Based on 100 parts by weight of polymethylene polyphenyl polyisocyanate, 0.8 parts of benzoyl chloride were diluted with anhydrous toluene and uniformly sprayed onto 1000 parts of dried converter steel slag (particle size 4.75~9.5mm, dried at 105℃ to constant weight, open porosity approximately 10%, surface pH approximately 12.0), and allowed to penetrate into the open pores of the converter steel slag under reduced pressure. Subsequently, the slag was treated at 60℃ under ventilation or reduced pressure for 20 minutes to remove inert solvents, volatile byproducts, and free benzoyl chloride from the surface, resulting in converter steel slag with passivated pore walls and no free acyl halide residue on the surface. The pH of the pore wall leachate was determined to be approximately 3.5 by the pH method.
[0049] Step S3: The converter steel slag with passivated pore walls and no free acyl halide residue on the surface obtained in step S2 is placed in the loading liquid obtained in step S1 until it is completely submerged. The vacuum is evacuated to -0.095MPa and held for 15 minutes. Then, the pressure is restored to normal, so that the loading liquid fills the open pores of the converter steel slag, and an interfacial hierarchical structure is obtained in the pores, which consists of alkaline pore walls, acidic passivation film and reactive loading material in sequence from the pore wall to the inside of the pore.
[0050] Step S4: While the impregnated converter slag is still hot, centrifuge it at 600 rpm for 45 seconds to remove the surface liquid and some of the loaded liquid at the orifice. According to the mass method, the filling degree of the reactive loading material in the open pores is about 75%, and the volume of the gas expansion cavity reserved at the orifice is about 25% of the volume of the open pores.
[0051] Step S5: After heating and melting the oxidized polyethylene wax, spray it onto the outer surface of the steel slag and water-cool it to form an encapsulation layer to obtain emulsified asphalt cold recycling functional aggregate.
[0052] Step S6: Mix 30 parts by mass of the obtained functional aggregate with 70 parts by mass of the recycled asphalt pavement material, then add 3.5% by mass of the total mass of the functional aggregate and the recycled asphalt pavement material of cationic slow-cracking fast-setting emulsified asphalt (solid content of about 60%) and 1.5% of added water, mix for 60 seconds and then form Marshall specimens.
[0053] Comparative Example
[0054] To verify the necessity of each core technical feature, the following comparative examples were set up. Each comparative example changed only one variable compared to Example 1. To facilitate repeated implementation, the preparation steps of each comparative example are described separately.
[0055] Comparative Example 1 (Neutral Carrier)
[0056] Step S1: By weight, mix 100 parts of polymethylene polyphenyl polyisocyanate with 15 parts of dehydrated 70# base bitumen, heat to 60°C and stir for 30 minutes to obtain an anhydrous loading liquid.
[0057] Step S2: Based on 100 parts by weight of polymethylene polyphenyl polyisocyanate, take 0.8 parts of benzoyl chloride, dilute with anhydrous toluene, and spray it evenly onto 1000 parts of dry basalt (particle size 4.75~9.5mm, open porosity of about 2%, surface pH value of about 7.2). After depressurized infiltration, treat it at 60℃ under ventilation or depressurized conditions for 20 minutes to remove solvent and volatile matter, and obtain the treated basalt.
[0058] Step S3: Place the basalt treated in step S2 into the loading liquid obtained in step 1, evacuate to a vacuum degree of -0.095MPa and maintain the pressure for 15 minutes, then restore to normal pressure to allow the loading liquid to fill the open pores of the basalt.
[0059] Step S4: While the impregnated basalt is still hot, centrifuge it at 600 rpm for 45 seconds to remove the surface liquid and some of the loaded liquid at the orifice, so that the filling degree is about 75%.
[0060] Step S5: Molten polyethylene wax is sprayed onto the outer surface of basalt and water-cooled to solidify, forming an encapsulation layer to obtain functional aggregate.
[0061] Step S6: Mix 30 parts by mass of the obtained aggregate with 70 parts by mass of the recycled asphalt pavement material, add 3.5% by mass of the total mass of the functional aggregate and the recycled asphalt pavement material of cationic slow-cracking fast-setting emulsified asphalt and 1.5% of the added water, mix for 60 seconds and then form Marshall specimens.
[0062] Comparative Example 2 (Full Hole)
[0063] Step S1: Mix 100 parts of polymethylene polyphenyl polyisocyanate with 15 parts of dehydrated 70# base bitumen, heat to 60°C and stir for 30 minutes to obtain an anhydrous loading liquid.
[0064] Step S2: Based on 100 parts by weight of polymethylene polyphenyl polyisocyanate, take 0.8 parts of benzoyl chloride, dilute it with anhydrous toluene, and spray it onto 1000 parts of dry converter steel slag. After depressurization infiltration, remove the solvent and volatiles under ventilation or depressurization conditions at 60°C to obtain converter steel slag with passivated pore walls.
[0065] Step S3: Place the passivated converter slag obtained in step S2 into the loading liquid obtained in step S1, evacuate to a vacuum degree of -0.095MPa and hold for 15 minutes, then restore to normal pressure, so that the loading liquid fills the open pores of the converter slag.
[0066] Step S4: The centrifugal cavity is cancelled. The impregnated steel slag is only naturally filtered to remove the outer surface liquid, so that the pores of the converter steel slag opening are close to full filling (the filling degree is close to 100%, and there is basically no reserved gas expansion cavity).
[0067] Step S5: Molten polyethylene wax is sprayed onto the outer surface of steel slag and water-cooled to solidify, forming an encapsulation layer to obtain functional aggregate.
[0068] Step S6: Mix 30 parts by mass of the obtained functional aggregate with 70 parts by mass of the recycled asphalt pavement material, add 3.5% emulsified asphalt and 1.5% water by mass of the total mass of the functional aggregate and the recycled asphalt pavement material, mix for 60 seconds and then form Marshall specimens.
[0069] Comparative Example 3 (without passivation film)
[0070] Step S1: Mix 100 parts of polymethylene polyphenyl polyisocyanate with 15 parts of dehydrated 70# base bitumen, heat to 60°C and stir for 30 minutes to obtain an anhydrous loading liquid.
[0071] Step S2: Cancel carrier pre-passivation, do not use benzoyl chloride, and take 1000 parts of dried converter steel slag for direct use.
[0072] Step S3: Place the unpassivated dry steel slag into the loading liquid obtained in step S1, evacuate to a vacuum degree of -0.095 MPa and maintain the pressure for 15 minutes, then restore to normal pressure, allowing the loading liquid to fill the open pores of the converter steel slag. In this step, the isocyanate is in direct contact with the unpassivated alkaline pore walls.
[0073] Step S4: While the impregnated converter slag is still hot, centrifuge it at 600 rpm for 45 seconds to remove the surface liquid and some of the loaded liquid at the orifice, so that the filling degree is about 75%.
[0074] Step S5: Molten polyethylene wax is sprayed onto the outer surface of steel slag and water-cooled to solidify, forming an encapsulation layer to obtain the functional aggregate. During sealed storage at 60℃, the isocyanate inside the pores undergoes alkali-catalyzed self-polymerization due to direct contact with the alkaline pore walls, gradually gelling and solidifying.
[0075] Step S6: Mix 30 parts by weight of the stored functional aggregate with 70 parts by weight of the recycled asphalt pavement material. Add 3.5% emulsified asphalt and 1.5% water (based on the total mass of the functional aggregate and recycled asphalt pavement material). Mix for 60 seconds and then form Marshall specimens. Because the pores have already gelled, the load is difficult to release and react normally during the use stage.
[0076] Comparative Example 4 (Passive Substitution)
[0077] Step S1: By weight, mix 100 parts of ordinary epoxy resin with an appropriate amount of latent curing agent (which does not produce gas when exposed to water), and heat to mix evenly to obtain a loading liquid.
[0078] Step S2: Take 1000 portions of dried converter steel slag, do not perform benzoyl chloride pre-passivation, and set it aside directly.
[0079] Step S3: Place the dried converter slag in the loading liquid obtained in step S1, evacuate to a vacuum degree of -0.095MPa and maintain the pressure for 15 minutes, then restore to normal pressure so that the loading liquid fills the open pores of the converter slag.
[0080] Step S4: Cancel the centrifugal cavity creation, so that the opening pores are close to the state of full pore filling.
[0081] Step S5: Molten polyethylene wax is sprayed onto the outer surface of steel slag and water-cooled to solidify, forming an encapsulation layer to obtain functional aggregate.
[0082] Step S6: Mix 30 parts by mass of the obtained aggregate with 70 parts by mass of the recycled asphalt pavement material, add 3.5% by mass of emulsified asphalt and 1.5% by mass of the total mass of the functional aggregate and the recycled asphalt pavement material, mix for 60 seconds and then form Marshall specimens.
[0083] Comparative Example 5 (Premixed Control)
[0084] Step S1: By weight, 100 parts of polymethylene polyphenyl polyisocyanate, 15 parts of dehydrated 70# base pitch and 0.8 parts of benzoyl chloride are added to the reactor, heated to 60°C and stirred for 30 minutes to obtain a loaded liquid containing benzoyl chloride, so that the acyl halide compound and isocyanate coexist in the same liquid phase.
[0085] Step S2: Take 1000 portions of dried converter steel slag, do not perform separate pre-passivation of the pore walls, and set it aside directly.
[0086] Step S3: Place the dried converter slag into the benzoyl chloride-containing loading liquid obtained in step S1, evacuate to a vacuum degree of -0.095MPa and maintain the pressure for 15 minutes, then restore to normal pressure so that the loading liquid fills the open pores of the converter slag.
[0087] Step S4: While the impregnated converter slag is still hot, centrifuge it at 600 rpm for 45 seconds to remove the surface liquid and some of the loaded liquid at the orifice, so that the filling degree is about 75%.
[0088] Step S5: Molten polyethylene wax is sprayed onto the outer surface of steel slag and water-cooled to solidify, forming an encapsulation layer to obtain the functional aggregate. During sealed storage at 60℃, the functional aggregate gradually thickens and local gelation occurs because benzoyl chloride and isocyanate coexist in the same liquid phase for a long time and the steel slag is not pre-passivated.
[0089] Step S6: Take 30 parts by mass of the stored functional aggregate and 70 parts by mass of the recycled asphalt pavement material and mix them together. Add 3.5% of the total mass of the functional aggregate and the recycled asphalt pavement material in emulsified asphalt and 1.5% of the added water. Mix for 60 seconds and then form Marshall specimens.
[0090] Comparative Example 6 (Over-passivation)
[0091] Step S1: Mix 100 parts of polymethylene polyphenyl polyisocyanate with 15 parts of dehydrated 70# base bitumen, heat to 60°C and stir for 30 minutes to obtain an anhydrous loading liquid.
[0092] Step S2: Based on 100 parts by weight of polymethylene polyphenyl polyisocyanate, take 5 parts of benzoyl chloride (the amount is significantly higher than the preferred range), dilute it with anhydrous toluene, and spray it onto 1000 parts of dry converter steel slag. After depressurization and penetration, remove the solvent and volatiles at 60°C, so that the alkalinity of the pore wall is excessively consumed, resulting in over-passivated steel slag.
[0093] Step S3: Place the over-passivated steel slag obtained in step S2 into the loading liquid obtained in step S1, evacuate to a vacuum degree of -0.095MPa and hold the pressure for 15 minutes, then restore to normal pressure, so that the loading liquid fills the open pores of the converter steel slag.
[0094] Step S4: While the impregnated converter slag is still hot, centrifuge it at 600 rpm for 45 seconds to remove the surface liquid and some of the loaded liquid at the orifice, so that the filling degree is about 75%.
[0095] Step S5: Molten polyethylene wax is sprayed onto the outer surface of steel slag and water-cooled to solidify, forming an encapsulation layer to obtain functional aggregate.
[0096] Step S6: Mix 30 parts by mass of the obtained functional aggregate with 70 parts by mass of the recycled asphalt pavement material, add 3.5% emulsified asphalt and 1.5% water by mass of the total mass of the functional aggregate and the recycled asphalt pavement material, mix for 60 seconds and then form Marshall specimens.
[0097] Performance test results and analysis:
[0098] In a set of exemplary tests, the results of the Marshall specimens molded from the mixtures prepared in Example 1 and each of Comparative Examples 1 to 6 are shown in the table below.
[0099] 24-hour early strength (kN) 7.8 3.5 4.6 - 4.3 4.5 4.0 7-day immersion residual strength compared to TSR (%) 92.5 82.0 87.0 - 85.5 84.0 84.0 Moisture content (%) after 24 hours of molding 2.0 3.6 3.4 3.6 3.5 3.3 3.3
[0100] Note: The table above shows a set of exemplary test results. Comparative Example 3, due to the cancellation of pre-passivation and direct contact between isocyanate and alkaline steel slag, resulted in in-pore gel failure during storage, preventing the loading material from being released and reacting normally during use. The corresponding mechanical and water stability indicators are marked as "-".
[0101] Alternative implementation methods:
[0102] The above embodiments use converter steel slag as the preferred carrier, but under the condition of having open pores and alkaline pore walls, the alkaline porous carrier can also be electric furnace steel slag, treated steel slag aggregate, calcium-containing alkaline industrial solid waste porous aggregate or a combination thereof, preferably with a surface pH value not lower than 11; the acyl halide compound used for pre-passivation can be acetyl chloride, p-nitrobenzoyl chloride and other acyl chloride compounds in addition to benzoyl chloride; the encapsulation layer can contain polyethylene wax, paraffin wax, microcrystalline wax or a hydrophobic polymer coating in addition to oxidized polyethylene wax, and can be formed by spraying, rolling, dipping or hot melt coating, etc.; the functional aggregate of the present invention can be used not only for emulsified asphalt cold recycled mixtures, but also for cold-mix cold-pave asphalt mixtures, cold patch materials and other water-containing mixed road maintenance materials that require water-triggered release or early reinforcement.
[0103] The foregoing has shown and described the basic principles, main features and advantages of the present invention. Various changes and modifications can be made to the present invention without departing from the spirit and scope thereof, and all such changes and modifications fall within the scope of the present invention as claimed.
Claims
1. A method for preparing emulsified asphalt cold recycled functional aggregate, characterized in that... The specific preparation steps are as follows: Step S1, Loading liquid compounding: By weight, 100 parts of polymethylene polyphenyl polyisocyanate are mixed with 10-20 parts of dehydrated matrix bitumen and heated to 55-65°C, and stirred for 25-40 minutes to obtain anhydrous loading liquid. Step S2, support pre-passivation: Based on 100 parts by weight of polymethylene polyphenyl polyisocyanate, 0.6~1.0 parts of acyl halide compound are diluted with an inert solvent and impregnated with a dry alkaline porous support under normal or reduced pressure, allowing it to penetrate into the open pores of the alkaline porous support. Benzoyl chloride reacts or adsorbs with the alkaline components on the pore walls of the alkaline porous support, forming an acidic passivation film in situ on the inner surface of the open pores of the alkaline porous support. Subsequently, the inert solvent and the volatile byproducts generated in the reaction are removed to obtain a support with passivated pore walls and no free acyl halide residue on the surface. Step S3, Vacuum Impregnation: The carrier with passivated pore walls and no free acyl halide residue on the surface obtained in Step S2 is placed in the loading liquid obtained in Step S1. The vacuum is drawn to a vacuum degree of -0.09~-0.098MPa and held for 10~20min. Then, the pressure is restored to normal, so that the loading liquid fills the open pores of the alkaline porous carrier and the acid passivation film is located between the inner surface of the open pores and the filled reactive loading material, forming an interfacial hierarchical structure of alkaline pore wall-acid passivation film-reactive loading material in the open pores of the alkaline porous carrier. Step S4, Centrifugal cavity creation: The alkaline porous carrier impregnated in step S3 is centrifuged to remove the surface liquid and part of the load liquid at the opening of the pores, so that the filling degree of the reactive load retained in the opening pores of the alkaline porous carrier is less than 100%, and a reserved gas expansion cavity is formed at the opening of the pores of the alkaline porous carrier. Step S5, Encapsulation: An encapsulation layer is applied to the outer surface of the alkaline porous carrier after centrifugation in step S4 and cured to obtain emulsified asphalt cold recycling functional aggregate.
2. The method for preparing emulsified asphalt cold recycled functional aggregate according to claim 1, characterized in that: In step S1, the polymethylene polyphenyl polyisocyanate is mixed with dehydrated matrix bitumen and heated to 60°C and stirred for 30 min; in step S2, the amount of the acyl halide compound is 0.8 parts, and the acyl halide compound is one or more of benzoyl chloride, acetyl chloride and p-nitrobenzoyl chloride; in step S3, the vacuum is drawn to a vacuum degree of -0.095 MPa and held for 15 min; in step S4, the alkaline porous carrier is centrifuged at 500~800 rpm for 30~60 s to make the filling degree of the reactive loading in the open pores of the alkaline porous carrier 70%~85%.
3. The method for preparing emulsified asphalt cold recycled functional aggregate according to claim 1, characterized in that: The loading liquid in step S1 also contains one or more of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, and isocyanate prepolymers. One or more of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, and isocyanate prepolymers are mixed with polymethylene polyphenyl polyisocyanate to adjust the reactivity, viscosity, and curing speed of the reactive loading material.
4. The method for preparing emulsified asphalt cold recycled functional aggregate according to claim 1, characterized in that: The alkaline porous carrier mentioned in step S2 is steel slag, and the alkaline component of the steel slag is one or more of free calcium oxide, calcium hydroxide and calcium silicate; the particle size of the converter steel slag is 4.75~9.5mm, the open porosity is 5%~20%, and the surface pH value is ≥11; the steel slag is specifically one or more of converter steel slag, electric furnace steel slag, treated steel slag aggregate and calcium-containing alkaline industrial solid waste porous aggregate.
5. The method for preparing emulsified asphalt cold recycled functional aggregate according to claim 1, characterized in that: In step S2, the benzoyl chloride is diluted with anhydrous toluene in an inert solvent and then impregnated with an alkaline porous support. The hydrogen chloride generated in the reaction evaporates or is consumed by the alkaline components of the pore wall of the alkaline porous support. The inert solvent is removed by short-term ventilation or gentle heating. The acidic passivation film is composed of calcium benzoate and residual acid, which maintains the pH value of the inner surface of the open pores of the alkaline porous support at 3.0~4.
0.
6. The method for preparing emulsified asphalt cold recycled functional aggregate according to claim 1, characterized in that: The volume of the gas expansion chamber in step S4 is 15% to 30% of the volume of the open pore.
7. The method for preparing emulsified asphalt cold recycled functional aggregate according to claim 1, characterized in that: The encapsulation layer in step S5 is oxidized polyethylene wax or a mixture of oxidized polyethylene wax with one or more of polyethylene wax, paraffin wax and microcrystalline wax. The storage stability and stirring trigger sensitivity of the functional aggregate can be adjusted by adjusting the composition and thickness of the encapsulation layer. The encapsulation method is spraying, rolling, dipping or hot melt coating.
8. The emulsified asphalt cold-recycled functional aggregate prepared by the method according to any one of claims 1 to 7, characterized in that: The functional aggregate comprises an alkaline porous carrier, an acidic passivation film located on the inner surface of the open pores of the alkaline porous carrier, a reactive loading material filling the open pores of the alkaline porous carrier, a gas expansion cavity located at the pore opening of the alkaline porous carrier, and an encapsulation layer located on the outer surface of the alkaline porous carrier. The acidic passivation film is used for interface passivation during the storage stage. During the storage stage of the functional aggregate, the alkaline components of the pore walls of the alkaline porous carrier are pre-passivated with an acyl halide compound, forming an acidic passivation film in situ on the inner surface of the open pores of the alkaline porous carrier. This shields the strongly alkaline nature of the alkaline porous carrier body into an acidic metastable state, allowing the subsequently filled highly reactive loading material, namely polymethylene polyphenyl polyisocyanate, to contact the acidic passivation film rather than the strongly alkaline components of the pore walls. This achieves stable storage of functional aggregates; the reactive loading material is used for release and solidification during the use stage. During the use stage of the functional aggregates, the addition of water during mixing dissolves and breaks through the acidic passivation film, causing the alkaline components on the pore walls of the alkaline porous carrier to be released again into a strongly alkaline active state. On the one hand, it catalyzes the reaction of the reactive loading material with water to generate gas in situ. The gas expands in the gas expansion chamber reserved at the opening of the pores of the alkaline porous carrier, changing the reactive loading material from passive displacement to active injection. On the other hand, it catalyzes the solidification of the ejected reactive loading material to generate polyurea and chemically consumes the water in the system, while simultaneously consuming the free alkaline groups on the alkaline porous carrier in situ. The gas expansion chamber is used for gas generation expansion and release during the use stage; the encapsulation layer is used for external protection during the storage and transportation stages.
9. The application of the emulsified asphalt cold recycling functional aggregate according to claim 8 in the preparation of emulsified asphalt cold recycling mixtures, cold-mixed and cold-laid asphalt mixtures, or cold patching materials.
10. The application according to claim 9, characterized in that: The emulsified asphalt cold recycling mixture comprises the emulsified asphalt cold recycling functional aggregate as described in claim 8, recycled asphalt pavement material, emulsified asphalt, and added water. By mass percentage, the emulsified asphalt cold recycling functional aggregate comprises 20%–40%, and the recycled asphalt pavement material comprises 60%–80%. Based on the total mass of the emulsified asphalt cold recycling functional aggregate and the recycled asphalt pavement material, the amount of emulsified asphalt is 3%–5%, and the amount of added water is 1%–2%. The emulsified asphalt is a cationic slow-cracking, fast-setting emulsified asphalt with a solid content ≥55%. During mixing, the added water enters the open pores of the alkaline porous carrier of the functional aggregate, destabilizing the acidic passivation film. The alkaline components on the pore walls of the alkaline porous carrier re-exert a catalytic effect, promoting the reaction of the reactive load with water. The gas generated by the reaction expands in the gas expansion chamber and pushes the reactive load out of the pores. The reactive load further reacts with water to generate a cured product containing urea groups or polyurea structures and consumes some water, thereby promoting the demulsification and early strength formation of the emulsified asphalt.